Rufibacter ruber sp. nov., isolated from fragmentary rock - Kýrová, Kamila; Sedláček, Ivo; Pantůček, Roman; Králová, Stanislava; Holochová, Pavla; Mašlaňová, Ivana; Staňková, Eva; Kleinhagauer, Tanita; Gelbíčová, Tereza; Sobotka, Roman; Švec, Pavel; Busse, Hans-Jürgen (International journal of systematic and evolutionary microbiology, 2016)
A red-pigmented, Gram-stain-negative, rod-shaped, aerobic bacterium, designated strain CCM 8646T, was isolated from stone fragments in James Ross Island, Antarctica. Strain CCM 8646T was able to grow from 10 to 40 °C, in the presence of up to 1 % (w/v) NaCl and at pH 7.0-11.0. Analysis of the 16S rRNA gene sequence placed strain CCM 8646T in the genus Rufibacter with the closest relative being Rufibacter roseus H359T (97.07 % 16S rRNA gene sequence similarity). The digital DNA-DNA hybridization values between strain CCM 8646T and R. roseus H359T were low (21.30±2.34 %). The major quinone was menaquinone MK-7. The polar lipids comprised phosphatidylethanolamine, an unknown aminoglycolipid and six unknown polar lipids. The G+C content of strain CCM 8646T was 51.54 mol%. On the basis of phenotypic, chemotaxonomic and genotyping results, strain CCM 8646T is considered to represent a novel species within the genus Rufibacter, for which the name Rufibacter ruber sp. nov. is proposed. The type strain is CCM 8646T (=LMG 29438T).
Keywords: zastoupení bazí; Cytophagaceae; vitamin K 2; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; Vitamin K 2; mastné kyseliny; fosfatidylethanolaminy; Phylogeny; Sequence Analysis, DNA; sekvenční analýza DNA; Nucleic Acid Hybridization; Antarktida; Soil Microbiology; Fatty Acids; hybridizace nukleových kyselin; Antarctic Regions; Pigmentation; DNA, Bacterial; DNA bakterií; Base Composition; Phosphatidylethanolamines; RNA ribozomální 16S; půdní mikrobiologie; Bacterial Typing Techniques; pigmentace